Persepsi mahasiswa terhadap dasar pengasingan penginapan mengikut gender: kajian perbandingan di Universiti Teknologi Malaysia (UTM), Skudai, Johor Dan Universiti Malaya, Kuala Lumpur - Basiron, Bushrah; Mustari, Mohd. Ismail; Marni, Nurazmallail; Muhammad, Azhar; Ahmad, Selmah; Mohd. Nor , Sulaiman Shakib (UTM, 2006)
Mixing among the teenagers may contribute to the decadency morals among the Malaysians especially among the students studying in higher institution (IPT). Many efforts have been done to overcome this problem and one of the practical ways that has been identified is to implement a new policy which is to separate the student based on their gender in hostels. Basically this study has been done to determine the importance, advantages and disadvantages of implementing this policy to all IPT in addition to prevent the decadency moral among the students. 382 students at Universiti Teknologi Malaysia, Skudai and 381 students at Universiti Malaya, Kuala Lumpur were chosen as respondents. Questionnaires were used and analyzed descriptively using Statistical Package for Social Sciences (SPSS). The reliability for this study is = 0.927. From the findings, most of the respondents agreed that the implementations of this policy are important to prevent the decadency morals in IPT and it will bring many benefits.